Hotel on the corner of bitter and sweet [compact disc, unabridged] : a novel - Ford, Jamie (Random House Audio, 2009)
When artifacts from Japanese families sent to internment camps during World War II are uncovered during renovations at a Seattle hotel, a man embarks on a quest that leads to memories of growing up Chinese in a city rife with anti-Japanese sentiment.